Lower Rates of Heart Failure and All-Cause Hospitalizations During Pulmonary Artery Pressure-Guided Therapy for Ambulatory Heart Failure: One-Year Outcomes From the CardioMEMS Post-Approval Study. (August 2020) - Shavelle, David M.; Desai, Akshay S.; Abraham, William T.; Bourge, Robert C.; Raval, Nirav; Rathman, Lisa D.; Heywood, J. Thomas; Jermyn, Rita A.; Pelzel, Jamie; Jonsson, Orvar T.; Costanzo, Maria Rosa; Henderson, John D.; et al.
Abstract : Background: Ambulatory hemodynamic monitoring with an implantable pulmonary artery (PA) sensor is approved for patients with New York Heart Association Class III heart failure (HF) and a prior HF hospitalization (HFH) within 12 months. The objective of this study was to assess the efficacy and safety of PA pressure-guided therapy in routine clinical practice with special focus on subgroups defined by sex, race, and ejection fraction. Methods: This multi-center, prospective, open-label, observational, single-arm trial of 1200 patients across 104 centers within the United States with New York Heart Association class III HF and a prior HFH within 12 months evaluated patients undergoing PA pressure sensor implantation between September 1, 2014, and October 11, 2017. The primary efficacy outcome was the difference between rates of adjudicated HFH 1 year after compared with the 1 year before sensor implantation. Safety end points were freedom from device- or system-related complications at 2 years and freedom from pressure sensor failure at 2 years. Results: Mean age for the population was 69 years, 37.7% were women, 17.2% were non-White, and 46.8% had preserved ejection fraction. During the year after sensor implantation, the mean rate of daily pressure transmission was 76±24% and PA pressures declined significantly. The rate of HFH was significantly lower at 1 year compared with the year before implantation (0.54 versus 1.25 events/patient-years, hazard ratio 0.43 [95% CI, 0.39–0.47], P <0.0001). The rate of all-cause hospitalization was also lower following sensor implantation (1.67 versus 2.28 events/patient-years, hazard ratio 0.73 [95% CI, 0.68–0.78], P <0.0001). Results were consistent across subgroups defined by ejection fraction, sex, race, cause of cardiomyopathy, presence/absence of implantable cardiac defibrillator or cardiac resynchronization therapy and ejection fraction. Freedom from device- or system-related complications was 99.6%, and freedom from pressure sensor failure was 99.9% at 1 year. Conclusions: In routine clinical practice as in clinical trials, PA pressure-guided therapy for HF was associated with lower PA pressures, lower rates of HFH and all-cause hospitalization, and low rates of adverse events across a broad range of patients with symptomatic HF and prior HFH. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02279888. Abstract : Supplemental Digital Content is available in the text.